The Effectiveness of Counseling Group Solution Focused Career to Increase Career Maturity Students of SMA Negeri 4 Pamekasan - Fitriyah, Fitriyah; Wibowo, Mungin Eddy; Japar, Muhammad (Jurnal Bimbingan Konseling, 2018)
This this study aims to test the effectiveness of group counseling solution focused career counseling to improve career maturity of students SMA Negeri 04 Pamekasan.The research design used was experiment involving 7 students from SMA Negeri 04 Pamekasan chosen by purposive random sampling. The instrument used in this research is Career Maturity Inventory (CMI) Form C. The results showed group counselling solution focused career counseling effectively to improve the maturity of career learners.This study provides clarification of the effectiveness of career maturity of learners with group counseling solution focused career counseling.